A prospective study on effectiveness of drotaverine in acceleration of labor - Dhungana, Padma Raj; Adhikari, Rajesh; Pageni, Prem Raj; Koirala, Apsara; Nepal, Anand (Medical Journal of Pokhara Academy of Health Sciences, 2019)
Background: Labor is a naturally occurring physiological process associated with uterine contractions, effacement, dilatation of cervix and descent of presenting part. Drotaverine hydrochloride is a non-anticholinergic isoquinoline derivative which acts by elevating intracellular cyclic Adenosine Mono Phosphate (cAMP) and cyclic Guanosine Mono Phosphate (cGMP) promoting smooth muscle relaxation.Materials and Method: This was a hospital based prospective study on effectiveness of Drotaverine Hydrochloride on enhancing dilatation of cervix and acceleration of active phase of labor. The sample size was 100. Fifty cases of women in active phase of labor received injection drotaverine hydrochloride 40 mg (group i) and fifty cases of women did not receive any drug (group ii) among those at term with singleton pregnancy and vertex presentation. Variables like maternal age, interval between administration of drug and delivery, mode of delivery, apgar score at 5 minutes, NCU (Neonatal Care Unit) admission and neonatal outcomes were recorded. Data analysis was done with the help of SPSS program.Results: The mean interval between drug administration to delivery in primipara and multipara in group i was 3.05 hours and 2.31 hours while in group ii was 4.5 hours and 3.75 hours respectively. The mean interval between drug administration and delivery was shorter in both groups of multipara. In group i, 96% had normal delivery and 4 % had vacuum delivery and in group ii 90% and 10% had normal delivery and vacuum delivery respectively. None of the participants had caeserian section. There were no perinatal mortalities.Conclusion: The administration of drug Drotaverine Hydrochloride is effective in shortening duration of labor with favorable feto-maternal outcome.